Exercise training remodels human skeletal muscle mitochondrial fission and fusion machinery towards a pro‐elongation phenotype. (1st December 2018) - Axelrod, Christopher L.; Fealy, Ciarán E.; Mulya, Anny; Kirwan, John P.
Abstract: Aims: Mitochondria exist as a morphologically plastic network driven by cellular bioenergetic demand. Induction of fusion and fission machinery allows the organelle to regulate quality control and substrate flux. Physiological stressors promote fragmentation of the mitochondrial network, a process implicated in the onset of metabolic disease, including type 2 diabetes and obesity. It is well‐known that exercise training improves skeletal muscle mitochondrial volume, number, and density. However, the effect of exercise training on muscle mitochondrial dynamics remains unclear. Methods: Ten sedentary adults (65.8 ± 4.6 years; 34.3 ± 2.4 kg/m 2 ) underwent 12 weeks of supervised aerobic exercise training (5 day/wk, 85% of HRMAX ). Body composition, cardio‐metabolic testing, hyperinsulinaemic‐euglycaemic clamps, and skeletal muscle biopsies were performed before and after training. MFN1, MFN2, OPA1, OMA1, FIS1, Parkin, PGC‐1α, and HSC70 protein expression was assessed via Western blot. Results: Exercise training led to improvements in insulin sensitivity, aerobic capacity, and fat oxidation (all P  < 0.01), as well as reductions in body weight, BMI, fat mass and fasting glucose (all P  < 0.001). When normalized for changes in mitochondrial content, exercise reduced skeletal muscle FIS1 and Parkin ( P  < 0.05), while having no significant effect on MFN1, MFN2, OPA1, and OMA1 expression. Exercise also improved the ratio of fusion to fission proteins ( P  < 0.05), which positively correlated with improvements in glucose disposal ( r 2  = 0.59, P  < 0.05). Conclusions: Exercise training alters the expression of mitochondrial fusion and fission proteins, promoting a more fused, tubular network. These changes may contribute to the improvements in insulin sensitivity and substrate utilization that are observed after exercise training.